Effect Of HESA-A On Acute Promyelocytic Cell Line(NB4) - Soodeh Namjoo; Fatemeh Nadali; Ahmad Kazemi; Hossein Dargahi; Hossein Rezaiezadeh; Shahrbanoo Rostami; Seyed Nasser Ostad (Tehran University of Medical Sciences, 2012)
Background and Aim: Acute leukemia is one of the main causes of cancer in the world. Now a days using natural materials as source of anticancer drugs is more recommended. HESA-A is a drug of herbal-marine origin (patented by Iranian researcher). HESA-A is composed of 50% inorganic substance، 45% organic substance (aminoenthraquinone) and 5% water. In this study effects of HESA-A، on NB4 cell line (Acute promyelocytic leukemia cells) was evaluated. Materials and Methods: HESA-A was prepared in normal saline as a stock solution (80 mg/ml, PH=7.4), and then was sterilized. After culturing and proliferation of NB4 cell line, the cells were treated by doses of 1, 2, 4 and 8 mg/ml of HESA-A. Respectively after 72h, the percentage of viable and dead cells were counted by using Trypan blue staining in Neubanr hemocytometer. Then by MTTassay, the percentage of cell survival were determined by ELISA reader in 570nm. Finally the effects of HESA-A on apoptosis were evaluated by flocytometery. Results: This invitro study shows that HESA-A has a cytotoxcic and antiprolifrative effects against NB4 cell line (Dose dependent).IC50 dose was 5mg/ml .HESA-A can result in apoptosis in 50% of the cells. Conclusion: Although the mechanism of HESA-A cytotoxicity action is not known, yet this study shows that this drug may cause apoptosis of cells by dose dependent method.